Instruments and methods for theranostic radioisotope production at the Bern medical cyclotron. Issue 1 (1st November 2022) - Dellepiane, G; Casolaro, P; Häffner, P D; Mateu, I; Scampoli, P; Voeten, N; Zyaee, E; Braccini, S
Abstract : Radioisotopes for theranostics are essential for nuclear medicine developments. Their production using solid target stations is challenging and new instruments and methods derived from particle physics are needed. A research program is ongoing at the 18 MeV Bern medical cyclotron, equipped with a solid target station and a 6 m long beam transfer line ending in a separate bunker. To irradiate 6 mm diameter compressed powder pellets, novel target "coins" were conceived and realized together with methods to assess the beam energy and the production cross sections. To measure the activity at End of Beam (EoB) a system based on a CdZnTe detector was installed. To accurately assess the properties of the beam, novel non-destructive one- and two-dimensional beam monitoring detectors were developed. An ultra-compact active irradiation system based on a novel magnetic lens and two-dimensional beam detectors was conceived and tested with the beamline and recently installed in an outport of the cyclotron.